Development Of A Control Flap For The Ultralight Helicopter - Zain, Mohammad Shair Mohd (Universiti Sains Malaysia, 2017)
The purpose of this project is to develop control flap for ultralight helicopter based on the concept of changing the airflow. The structure of the control flap was analyzed based on the extreme condition. The control flap consists of two materials which are Aluminum (2014-T4) and PF. The maximum Von Mises stresses obtained from the simulation was 38.75MPa. The results obtained from FEA do not exceed safety factor of 1.5 based on airworthiness requirement. Thus the structure of control flap is assumed to be safe and will not fail. For verification of the FEA software, a simple case of deflection of beam and plate were conducted and compared with the theoretical calculation. The results from both of theoretical and FEA were compared and the differences are 3.72% and 1.48% for beam and plate respectively. The results are acceptable since the differences are lower than 5%.